PREFABRICATED MULTICELLS SILOS MODULES IN CONCRETE - da SILVA, Eduardo Teixeira (Scientia Agraria, 2002)
This research work was developed to provide technical information for designing multicells reinforced concrete prefabricated silos, in square form and 60 tons to 15 tons corn capacity per cell, aiming small and medium agricultural producers. Theoretical and experimental analyses were conducted that the two coupled by appluing a model of element to evaluate the strutural behavior of a real scale separated elements and coupled elementand coupled element which form the square wall of the modular silo. From the experimental analysis it was concluded that the two coupled element model presented a satisfactory behavior where toughest spot. The stress values obtained from the RAVENETS method and from the biarticulable beam theory were lower than the values experimentally obtained. The measured displacement exhibited similar behavior, however greater than the values calculated by applying the maximum inflection and the half shaft inflection method.